Lecteurs anciens du Code Théodosien : l’interprétation wisigothique - Federico Battaglia (Clio@Themis, 2023)
Several types of texts in the Late Antique West share an intertextual relationship with the Theodosian Code, giving rise to a “second degree” legal literature. The study of this intertextual network provides the background for analyzing the Visigothic interpretationes of the Theodosian Code, which belongs to the network. In turn, the specificity of Visigothic rewriting of the Roman constitutions is compared to how, in the East, Justinian reworked the imperial laws of previous centuries.